Home Health Utilization in Assisted Living Settings. (December 2020) - Nazareno, Jennifer; Zhang, Wenhan; Silver, Benjamin; Dosa, David; Gozalo, Pedro; Thomas, Kali
Home health agencies (HHAs) are one of the most commonly used third-party providers in the assisted living (AL) setting. One way ALs may be potentially able to meet the needs of their residents despite increased impairment is through supplementing the services offered with those delivered by HHAs. We explore the growth in the delivery of HHA services to Medicare beneficiaries in AL compared with other home settings between 2012 and 2014. We also examine demographic, cognitive, and functional characteristics of beneficiaries; HHA provider characteristics; and the variation in the percentage of home health use in ALs across the country. Our findings suggest that there was a slight growth in the share of HHA services being delivered in AL. HHA recipients in AL were more likely to have cognitive and activities of daily living impairments than those receiving HHA services in other settings. This is among the first studies to examine HHA utilization in AL.